Efeito residual da adubação nitrogenada e molibídica no milho sobre a soja cultivada em sucessão - Caioni, Sheila [UNESP]; Lazarini, Edson [UNESP]; Parente, Tiago de Lisboa [UNESP]; Bossolani, João William [UNESP]; de Souza, Luiz Gustavo Moretti [UNESP]; Pivetta, Raul Sobrinho [UNESP]; Dickmann, Lourdes [UNESP] (My University, 2017)
This research aimed evaluates the residual effect of molybdenum (Mo) and nitrogen (N) in soybean cropping in succession to corn. The experiment was conducted in Selviria, MS, Brazil, in a randomized complete block with split plots, with four nitrogen rates (0, 90, 135 and 180 kg ha1) and five doses of Mo (0, 10, 20, 30 and 40 g ha1), with four replications. There was residual effect, being for Mo, the dose of 28 g ha1 promoted the highest soybean grain yield. For the N, there was a linear increase in productivity, reaching 3593 kg ha1 of grain.
Residual effect of nitrogen and molybdenum fertilization at the corn on the soybean cultivated in sequence
Keywords: Glycine max; Micronutrient; Molybdenum and nitrogen